Correlation between Physical Workload and Musculoskeletal Disorders Complaints among Nurses at Hospital - Heni Fa’riatul Aeni; Lilis Banowati; Tuti Nur’alinda (Universitas Airlangga, 2020)
Introduction: Musculoskeletal disorders complaints occur due to excessive muscle contraction, excessive workloads and monotonous movements such as when nurses perform various nursing task such as moving patients, carrying patients from bed to wheelchair, awkward posture during infusion placement. This study aims to determine the correlation between physical workload and musculoskeletal disorders complaints among nurses at Regional General Hospital (RSUD) of Indramayu District in 2019. Methods: The design of this study uses quantitative with cross sectional. The method of data collection was crried by means of interview using the Nordic Body Map (NBM) questionnaire and observing the pulse calculation manually using a watch. Among the populations of 348 nurses, the samples of 75 nurses were selected based on the accidental sampling method. Statistical test used the chi-square test with a confidence level of 95% (α=0.05). Results: The study findings showed that most of 40 nurses who had heavy physical workload, 35 nurses (87.5%) had high musculoskeletal disorders complaints and 5 nurses (12.5%) had moderate musculoskeletal disorders complaints. On the other hand, of the 35 nurses who had moderate physical workload, 26 nurses (74.3%) experienced moderate musculoskeletal complaints and 9 nurses (25.7%) had high musculoskeletal disorders complaints. Chi-Square test results obtained p value = 0.000 (p <0.05). Thus, it can be concluded that there was a significant correlation between physical workload and musculoskeletal disorders complaints among nurses. Conclusion: The heavier the physical workload, the higher the musculoskeletal disorders complaints among nurses.Keywords: musculoskeletal disorders, nurses, physical workload